How sports-implied packaging of protein powder products enhances the purchase intention of Generation Z: evidence from multiple experiments - Hu, Chang; Bin, Junhao; Zhang, Wen; Huang, Wenying (Frontiers in Nutrition, 2025)
BackgroundIn recent years, Generation Z's demand for protein powder and other sports nutrition products has grown significantly. While existing studies have primarily focused on how product functionalities influence consumer decisions, the decision-triggering mechanisms of packaging design within the framework of sensory marketing theory remain unclear. Specifically, the psychological pathways through which sports-implied elements influence Generation Z's purchasing decisions remain underexplored.MethodBased on embodied cognition theory and self-determination theory, this study employs a mixed research methodology to conduct three online scenario experiments (N = 1,456). We examined the impact of sports-implied packaging on Generation Z's purchase intention using two-way ANOVA and Process Model 6 to test the moderating role of disease threat and the chained mediating roles of exercise motivation and psychological empowerment.ResultsCompared to traditional packaging, sports-implied packaging significantly enhances Generation Z's purchase intention. In this process, Generation Z's exercise motivation and psychological empowerment further amplify the stimulating effect of sports-implied labels, strengthening their purchase intention. Notably, the intensifying role of intrinsic motivation is particularly pronounced. Additionally, higher levels of disease threat magnify the promoting effect of sports implications.ConclusionThis study provides theoretical support for protein powder manufacturers to develop precise marketing strategies. It is recommended that companies optimize packaging designs based on disease threat levels, psychological empowerment, and exercise motivations based on their target demographics.